Managing Software Project Risks (Implementation Phase) With Proposed Regression Analysis Techniques - Abdelrafe, E.; Hussin, B. (2013)
Regardless how much effort we put for the success of software project, many software projects have very high failure rate andrisks are everywhere in life. Risk is not always avoidable but it is controllable the aim of this paper is to present new techniques by which we can study the impact of different risk management techniques and different risk factors on software development project and redusing risk with software process improvement. Top ten software risk factors (implementation phase)and thirty control factors were presented to respondets. The results show that all risks in software projects were presented to respondets. The Perspective, whereas all controls are used most of time and often. These test were performed using regression analysis to compare the controls to each of the risk factors in Table XLVI. The study has been conducted on a group of software project managers. Successful project risk management will greatly improve the probility of project succes.